2019
DOI: 10.1186/s12879-019-4390-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of TGF-ß1 polymorphisms and chronic hepatitis C infection: a Meta-analysis

Abstract: Background Although several researches have reported the connection between the transforming growth factor-beta 1 ( TGF-β1 ) gene polymorphisms and chronic hepatitis C virus (HCV) infection, the conclusions of these studies were not always consistent. Here, this paper proposed a meta-analysis to evaluate whether the TGF-ß1 gene polymorphisms, −509C/T (rs1800469), codon 10 T/C (rs1982073) and codon 25G/C (rs1800471), were associated with chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
9
1
Order By: Relevance
“…Although several epidemiological studies have examined the association of TGF-β1 Arg25Pro (G>C) variant with the chronic HCV infection susceptibility, and fibrosis progression, controversial results still exist (Gewaltig et al, 2002;Pereira et al, 2008;Guo et al, 2019). In the current study we did not find significant difference in genotyping distribution or allele frequency of TGF-β1 (Arg25Pro) variant when comparing total cirrhosis patients with controls.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Although several epidemiological studies have examined the association of TGF-β1 Arg25Pro (G>C) variant with the chronic HCV infection susceptibility, and fibrosis progression, controversial results still exist (Gewaltig et al, 2002;Pereira et al, 2008;Guo et al, 2019). In the current study we did not find significant difference in genotyping distribution or allele frequency of TGF-β1 (Arg25Pro) variant when comparing total cirrhosis patients with controls.…”
Section: Discussioncontrasting
confidence: 67%
“…However, the subjects with codon 25 G allele which was associated with high TGF-β1 production displayed over suppression in the human immune response. This mechanism may elucidate the correlation of the polymorphism of Arg25Pro (G>C) and chronic HCV infection (Guo et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…These findings are different with some past studies that indicated an association of the gene polymorphism of the TGF-β1 genotype with the outcome of HCV infection [ 14 ]. By contrast, several studies that explored the role of TGF-β1 rs1800471 (the codon 25G) polymorphism in chronic HCV infection in Asian, Caucasian, and Brazilian populations found no significant association between the codon 25G/C polymorphism and chronic HCV infection in all subgroup analyses [ 16 , 34 , 35 ]. The human TGF-β1 gene located on chromosome 19q13 is mainly expressed by regulatory T cells [ 36 ].…”
Section: Discussionmentioning
confidence: 92%
“…Transforming growth factor-beta (TGF-β) is a cytokine secreted by hepatic stellate cells, fibroblasts, Kupffer cells, and M2 macrophages that regulate cell growth, differentiation, and proliferation [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%